PENGELOLAAN VEGETASI DI KAWASAN EKOWISATA MANGROVE PERANCAK, JEMBRANA - Sundra, I Ketut; Mahendra Dewi, Ni Luh Putu (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2024)
Perancak mangrove forest is one of the important supporters for mangrove ecotourism in perancak as an ecosystem that functions ecologically, economically and socially as an effort to preserve the beach in a sustainable manner. This research aims to determine the level of diversity of mangrove vegetation types in the perancak coastal area and conduct mangrove management efforts through vegetation analysis and soil analysis. Sampling carriedout on true mangroves and associated mangroves using purposive sampling technique. The method of flora sampling was carried out by quadrant method by calculating the important value index, diversity index and type distribution pattern.  True mangroves consist of 13 species and 1367 individuals, dominated by rhyzophora stylosa, with a total importance index (indeks nilai penting)= 299.86 % (classified as sestable), diversity index 1.1192 and distribution pattern = 0.548 (vegetation is stable and uniform).  Associate mangroves  consists of 13 types and 649 individuals, dominated by the type Terminalia cattapa. Important index =297.892 %, diversity index = 0.9438 and type distribution pattern = 0.73 i.e vegetation that grows is classified as uniform. Analysis results for the 5 soil samples for total n, p and k elements available and organic c, all support mangrove growth. the development of true mangroves and associations is the main supporting factor for the development of tourism areas in the perancak jembrana ecotourism area which is now developing into a beach park developed by the people of Perancak village. Keywords: Perancak; Mangrove Diversity; Management; Soil Analysis